Thermodynamic model and viscosity of As-Se glasses - Chovanec, Jozef; Shánělová, Jana; Málek, Jiří (University of Pardubice, 2014)
This work is focused on study of structure and viscosity relationship of As-Se glass melts. The structure was described by the thermodynamic model (or model of association solutions) of Shakhmatkin and Vedishcheva. The system contains five components (As, Se, AsSe, As2Se3, As4Se3) according to the phase diagrams. In this model, we consider only four components because the last one is in linear dependence on the As amounts. For a description of experimental viscosity values, we used the regular Adam & Gibbs, Avramov and Milchev and MYEGA viscosity equations. The thermodynamic model described the structural units in the As-Se undercooled glasses with sufficient precision. The best fit of viscosity data was achieved using the Adam & Gibbs model.